Keadilan Sosial Bagi Pasien Pengguna Bpjs Dalam Memperoleh Layanan Kesehatan Dalam Perspektif Konseling Multikultural - Yuwinda Ardila (Program Studi Bimbingan dan Konseling FKIP UMSU, 2018)
Health as human rights is a very important thing to fight for, because health is the cause of the quality and future of a nation. To ensure the health of all levels of society in a nation, health insurance is needed in order to facilitate the poor and less able to obtain their rights as human beings. But social justice often does not take sides with the lower classes so that their rights are ignored by those who should be responsible. It is hoped that the government will pay more attention to the rights of its people equally so that it does not cause social inequality, because the fifth principle reads